Proliferation and Survival Signaling from Both Jak2-V617F and Lyn Involving GSK3 and mTOR/p70S6K/4EBP1 in PVTL-1 Cell Line Newly Established from Acute Myeloid Leukemia Transformed from Polycythemia Vera - Nagao, Toshikage (Public Library of Science, 2014)
The gain of function mutation JAK2-V617F is very frequently found in myeloproliferative neoplasms (MPNs) and is strongly implicated in pathogenesis of these and other hematological malignancies. Here we report establishment of a new leukemia cell line, PVTL-1, homozygous for JAK2-V617F from a 73-year-old female patient with acute myeloid leukemia (AML) transformed from MPN. PVTL-1 is positive for CD7, CD13, CD33, CD34, CD117, HLA-DR, and MPO, and has complex karyotypic abnormalities, 44,XX,-5q,-7,-8,add(11)(p11.2),add(11)(q23),−16,+21,−22,+mar1. Sequence analysis of JAK2 revealed only the mutated allele coding for Jak2-V617F. Proliferation of PVTL-1 was inhibited and apoptosis was induced by the pan-Jak inhibitor Jak inhibitor-1 (JakI-1) or dasatinib, which inhibits the Src family kinases as well as BCR/ABL. Consistently, the Src family kinase Lyn was constitutively activated with phosphorylation of Y396 in the activation loop, which was inhibited by dasatinib but not by JakI-1. Further analyses with JakI-1 and dasatinib indicated that Jak2-V617F phosphorylated STAT5 and SHP2 while Lyn phosphorylated SHP1, SHP2, Gab-2, c-Cbl, and CrkL to induce the SHP2/Gab2 and c-Cbl/CrkL complex formation. In addition, JakI-1 and dasatinib inactivated the mTOR/p70S6K/4EBP1 pathway and reduced the inhibitory phosphorylation of GSK3 in PVTL-1 cells, which correlated with their effects on proliferation and survival of these cells. Furthermore, inhibition of GSK3 by its inhibitor SB216763 mitigated apoptosis induced by dasatinib but not by JakI-1. Together, these data suggest that apoptosis may be suppressed in PVTL-1 cells through inactivation of GSK3 by Lyn as well as Jak2-V617F and additionally through activation of STAT5 by Jak2-V617F. It is also speculated that activation of the mTOR/p70S6K/4EBP1 pathway may mediate proliferation signaling from Jak2-V617F and Lyn. PVTL-1 cells may provide a valuable model system to elucidate the molecular mechanisms involved in evolution of Jak2-V617F-expressing MPN to AML and to develop novel therapies against this intractable condition.